2019
DOI: 10.1017/s0022109019000061
|View full text |Cite
|
Sign up to set email alerts
|

Googling Investor Sentiment around the World

Abstract: We study how investor sentiment affects stock prices around the world. Relying on households’ Google search behavior, we construct a weekly measure of sentiment for 38 countries during 2004–2014. We validate the sentiment index in tests using sports outcomes and show that the sentiment measure is a contrarian predictor of country-level market returns. Furthermore, we document an important role of global sentiment in stock markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(53 citation statements)
references
References 88 publications
2
49
0
2
Order By: Relevance
“…This choice is based on two considerations. First, the selected indirect measures have been used by some of the important studies, for instance, Brown and Cliff, Baker and Wurgler, Chen et al, Fisher and Statman, and Gao et al [10,12,13,39,79,80]. Second, GSVI is a unique direct measure of sentiment on which time series can be constructed and combined with data on indirect measures.…”
Section: Measurement Of Sentimentmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice is based on two considerations. First, the selected indirect measures have been used by some of the important studies, for instance, Brown and Cliff, Baker and Wurgler, Chen et al, Fisher and Statman, and Gao et al [10,12,13,39,79,80]. Second, GSVI is a unique direct measure of sentiment on which time series can be constructed and combined with data on indirect measures.…”
Section: Measurement Of Sentimentmentioning
confidence: 99%
“…The Harvard IV-4 Dictionary and the Lasswell Value Dictionary are used for developing the set of finance and economic related search terms. Following Gao et al [80], the steps given below are performed for developing Google search volume index (GSVI):…”
mentioning
confidence: 99%
“…First, uses of the same international search engine for all countries make the data consistent and comparable. Our approach is similar to Gao et al (2016), who study the Google sentiment on stock markets in a cross country analysis around the globe, including mainland China. Second, though Google search is prohibited in the mainland China, foreign retail investors are still able to use Google to search information and decide to trade in the Chinese stock markets or local investor can use the virtual private networks (VPNs) to access the Google website (Wang et al 2017).…”
mentioning
confidence: 99%
“…Challet and Ayed [16] wrote that Google Trends data are aggregate signals generated by many individuals and are related to the underlying assets and further concluded that Google Trends data are equivalent to price returns. Based on datasets from 40 countries for 2004-2014, Gao, Ren and Zhang [20] found that a sentiment measure using Google Trend data is significantly associated with country-level stock market returns. Yu, Zhao, Tang and Yang [50] reported that Google trends data can significantly associated with oil consumption.…”
Section: Independent Variable-chinese Influencementioning
confidence: 99%